URGENSITAS SISTEM PEMILU PROPORSIONAL TERBUKA BERDASARKAN DEMOKRASI PANCASILA - Ika Puspahani; Mohammad Saleh (Jurnal HUKUM BISNIS, 2023)
This paper aims to determine the urgency of an open proportional general election system in the 2024 general election. The research method uses normative legal research, using a statutory approach and a conceptual approach. The focus of this research plan is the general election system (election) based on the constitution. In theory there are two general election systems, namely the district and proportional systems. The proportional system is seen as having strong protection for maintaining plurality or a large number of political parties, because of the treatment that there are no invalid votes and there is a possibility that each political party in an electoral district is able to place its representatives in a representative institution, regardless of the number. This study considers it important to study the correlation of the proportional system in general elections with the spirit of implementing Pancasila democracy.Keywords: Election, proportional system, democracy